Performance study of Different Staging Patterns on Elevated Intze Tank according to IS 1893 (Part –II) 2014 - Sharma, Ayush; Amritpal Singh, Dr. (IJRDO - Journal of Mechanical And Civil Engineering, 2018)
This research paper compares the performance of Elevated Intze water tanks with the different staging patterns in context of their 1] Base shear 2] Overturning moments 3] Stress variations     4] Area of Steel. The design basis furnished in IS 1893-1984 for elevated water tanks are based on one-mass idealization of elevated water tanks which is not appropriate for large (large width to depth ratio) and partially filled tanks. Also the design features of this standard lead to very weak and slender support system which renders the superstructure quite vulnerable in the high seismic area. Also the seismic forces so suggested by this standard are the same as that for the most ductile building framing system. The code does not take into account the convective and impulsive pressure which in turn comes in role during horizontal excitations. Therefore the objective of this study is to assess the impression of seismic forces on two type of tank systems differentiated on the basis of their supports classified as Framed Staging and Shaft Staging. The analysis of the systems is carried out using Response Spectrum Analysis and the behavior of these staging systems is analyzed as per IS 1893 (Part 2) 2014.